Relationship capital mediation in the internationalization - Deszczyński, Bartosz; Dymitrowski, Adam; Fonfara, Krzysztof (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The cornerstone of this paper is the assumption that in order to accelerate the internationalization process, companies trying to enter foreign markets have to “borrow” relationship capital from one or several mediating agents. The concept of relationship mediating agents fits into the network approach to internationalization and explains why entities with a dense network of connections tend to be more successful than single players. Aim: To examine the phenomenon of relationship capital mediation by different actors (agents) in the internationalization process as to the availability of these agents and their impact on the success of internationalization process. Results: The network perspective on internationalization is refined through the concept of relationship capital mediation. The paper introduces a typology of RCMA and outlines the relationship resources they provide in different timeframes related to the internationalization process, before, during and after the actual business project.